Characteristics of the fundus and optical coherence tomography angiography metrics in myopic patients with myelinated retinal nerve fibers - Weiming Yang; Ruoyan Wei; Chi Zhang; Chen Huang; Feng Lin; Yang Shen; Chenhao Yang; Xingtao Zhou; Meiyan Li (BMC Ophthalmology)
Abstract Aims To investigate the fundus characteristics and macular optical coherence tomography angiography (OCTA) metrics in patients with myelinated retinal nerve fibers (MRNF) and to identify the associations among myopic parameters, fundus metrics, and OCTA metrics. Methods The single-center case-control study included 15 patients with monocular MRNF and 15 patients without MRNF, matched for age, affected eyes’ spherical equivalent error (SER), and axial length (AL) between May 2021 and December 2021. Fundus features, including the entire MRNF area (Area1), the denser MRNF area (Area2), and the shortest distance from the fovea to the MRNF border (Df−m), along with ocular parameters, including SER, AL, best corrected visual acuity (BCVA), and OCTA metrics at the fovea, including choroidal (ChT) and retinal (ReT) thicknesses at the fovea, the foveal avascular zone area (FAZ), foveal avascular zone perimeter (FAZP), FAZ-circularity index (FAZ-CI), and foveal vessel density in a 300-µm wide region (FD-300), were assessed. Results The SER, AL, and BCVA were significantly different, and the ChT was thinner in the affected eyes than in the contralateral eyes. Compared with matched eyes, affected eyes had reduced BCVA and thinner ReT. In the affected eyes, both Area1 and Area2 were negatively correlated with SER (r 1 = -0.84, r 2 = -0.65), △SER (r 1 = -0.86, r 2 = -0.61), ReT at the vertical superior 3 mm (VS) (r 1 = -0.78, r 2 = -0.67), and ChT_VS (r 1 = -0.64, r 2 = -0.62), and positively correlated with AL (r 1  = 0.82, r 2  = 0.52) and BCVA (r 1  = 0.54, r 2  = 0.59). Df−m was negatively correlated with BCVA (r = -0.57). Conclusion The presence of MRNF affects BCVA and ReT at the fovea. The area of the MRNF, as well as the distance from the MRNF to the fovea, are closely associated with the affected eyes’ BCVA, SER, AL, and the degree of anisometropia.